Meluruskan Pola Pikir Umat Mengenai Keimanan Ahli Kitab dalam Alquran dan Implikasinya terhadap Toleransi Beragama - Abdul Munim Amaly; Munawwar Rahmat (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2018)
When people say Ahli Kitab, the Muslims views tend to lead to infidels. But is that so? Is Ahli Kitab are infidels? Or are they believers? The purpose of this study is to explore the truth in the perspective of the Qur'an and its implications for religious tolerance. By using the method of